Codification of Local Wisdom Themes in Indonesian Language Teaching Materials to Foster National Defense Spirit in Border Regions - Yanti, Prima Gusti; Safii, Imam; Ermawati , Imas Ratna; Rahman, Fauzi; Zabadi, Fairul; Hidayati, Deasy Wahyu (Journal of Ecohumanism, 2025)
The national defense attitude of most students in Indonesia’s border regions must be enhanced. Therefore, developing teaching materials that can support the improvement of these students’ national defense attitudes is necessary. This research aims to code relevant themes based on local wisdom to build the spirit of national defense among students in Indonesia’s border regions, particularly in North Kalimantan. This study employs a qualitative approach using interview and documentation techniques. Data analysis is conducted through four stages: data reduction, data display, conclusion drawing, and verification. Based on research on the local wisdom content and national defense values present in the traditions of the North Kalimantan community, several themes can be codified to serve as a foundation for developing Indonesian language teaching materials. These themes include strengthening national identity, character and moral formation, education, and socialization, as well as cultural resilience and national defense.